Integrating data from multiple surveys and accounting for spatio-temporal correlation to index the abundance of juvenile Pacific halibut in Alaska. (23rd September 2017) - Ono, Kotaro; Ianelli, James N; McGilliard, Carey R; Punt, André E
Abstract: Survey indices of abundance are one of the main sources of information used in fish stock assessment. Many regions around the world, including the United States and Europe, develop survey protocols to aid in creating these indices. As ecosystems function as a continuum across borders, there is a need to develop a standardized framework for combining information across surveys. Such methods could help resolve differences in timing, spatial coverage, catchability, and selectivity among surveys. We present a method that uses survey data by length class. These data come from several regional surveys each with differing sampling designs, spatial and temporal coverage, and sampling gear. The method accounts for the spatio-temporal correlation structure in length-specific catch rates and occurrence, and allows for differences in catchability and selectivity among regions. The approach was applied to Pacific halibut ( Hippoglossus stenolepis ) in Alaska, a broadly distributed species for which there is considerable uncertainty in recent recruitment estimates. Results confirm the major recruitment event of 1987 recorded in the most recent stock assessment and also detected recruitment peaks in more recent years (1998 and 2004–2005). The signal seems to be mostly related to the Eastern Bering Sea shelf survey data. The approach introduced in this study is general and could be expanded to other regions and species where standardized survey data are collected that include extensive length and/or age measurements.